Analisis Peran Orang Tua Terhadap Motivasi Belajar Anak Usia Sekolah Dasar Pada Masa Pandemi Covid-19 - Anna Rika Rakhim; Kiswoyo Kiswoyo; Asep Ardiyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research describes an event that occurred in the field related to the role of parents in the learning motivation of grade III elementary school age children during the co-19 pandemic. The type of research used is descriptive qualitative to seek and find understanding of phenomena in a specific context. The data in this study are in the form of questionnaires, interviews, and documentation. The results of the analysis show that during the Covid 19 pandemic the role of parents was needed in the learning process of students. The role of parents in education is the expected behavior of parents (father and mother) in the form of responsibilities and functions that must be carried out as the main and first educators for children to shape the child's personality. Meanwhile, learning motivation is an encouragement in students that causes learning activities both from within and outside themselves so that the desired goals can be achieved. Parents can provide motivation, attention, appreciation, facilities, and support for children during learning activities at home.